Self-Myofascial Release Effect With Foam Rolling on Recovery After High-Intensity Interval Training - Laffaye, Guillaume; Da Silva, Debora Torrinha; Delafontaine, Arnaud (Frontiers in Physiology, 2019)
The goal of this experiment was to assess the impact of self-myofascial massage with the aid of a foam roller on a lower limb immediately after high-intensity interval training (HIIT), using the Tabata protocol (20 seconds work / 10 seconds rest, repeated 8 times), according to selected recovery variables. The method used Tabata squats (20 seconds of air squats / 10 seconds of rest, repeated 8 times), after which the subject performed three series of self-myofascial massage with a foam roller on one leg, the other leg being used as the control. Biomechanical lower-limb performance was assessed through a squat jump, a countermovement jump and a hopping on the spot test. Flexibility was assessed through the active and passive range of motion at the hip, knee and ankle. Pain was measured by recording the delay of muscle soreness (DOMS). Measurements were recorded immediately after the workout, then 24 hours and 48 hours later. 20 healthy males participated in the study. The results revealed no effect on jumping performance, in terms of height, leg stiffness, power or force output. Additionally, HIIT had a significant impact on muscle damage, as revealed by the reduction in performance 48 hours later (-9.7% for the countermovement height). The self-myofascial release decreased DOMS by 50% for the massaged leg compared with 20% for the control leg and increased the hip range of motion by approximately 4.2% for the massaged leg in comparison with the unmassaged leg. This experiment reveals the poor effect of self-myofascial release on regaining the initial value of performance but could be useful for reducing DOMS after high-intensity interval training.